Synthesis, Photophysical, Electrochemical Properties and Charge-Transfer Complexation Studies of Piperazinophanes - Thirunarayanan, Ayyavu; Rajakumar, Perumal (Synlett, 2014)
Several 1:1 and 2:2 oligomeric forms of piperazinophanes with oxa–aza intraannular functionalities and containing various bicyclic ring systems as spacer units were prepared by a one-pot method under simple and mild conditions through a multicomponent reaction strategy involving a Mannich reaction. All the piperazinophanes exhibited absorption maxima in the range 242–356 nm and emission bands between 432 and 501 nm. The photophysical behaviors of the piperazinophanes and their binding properties for 7,7,8,8-tetracyanoquinodimethane, ethylene-1,1,2,2-tetracarbonitrile, and paraquat were examined.
Keywords: supramolecular chemistry; photochemistry; host–guest systems; electrochemistry; cyclophanes